HMGA2/PHGDH axis-mediated glycolysis under hypoxia is required for cadmium-induced A549 cell migration - Chunpeng Gao; Qiuxuan Xie; Li Li; Shengxiang Luo; Jianhui Fan; Jun Cao (Ecotoxicology and Environmental Safety)
Cadmium (Cd) is a widespread environmental contaminant, which has been classified as a human carcinogen. Phosphoglycerate dehydrogenase (PHGDH), the first rate-limiting enzyme involved in the serine biosynthesis pathway, was reported to be able to indicate poor prognosis for cancers. In this study, we investigated the possible mechanism of PHGDH in Cd-induced cell migration. Firstly, 2 μM Cd increased the expression of PHGDH protein in A549 cells and HELF cells. Similarly, Cd exposure (0.5 and 1 mg/kg) led to increased PHGDH expression in lung tissue of male BALB/c mice. Silencing PHGDH suppressed Cd-triggered aerobic glycolysis while enhancing oxidative phosphorylation (OXPHOS), suggesting that PHGDH plays a critical role in the metabolic adjustments caused by Cd exposure. Secondly, the heightened expression of HMGA2 triggered PHGDH, and the Chromatin immunoprecipitation (ChIP) assay revealed HMGA2 protein binds directly to the promoter region of the PHGDH gene. Furthermore, HMGA2/PHGDH axis was determined to be involved in Cd-induced aerobic glycolysis. Using CoCl2 (100 μM) to induce hypoxia and YC-1 (10 μM), the inhibitor of HIF-1α, we demonstrated that HIF-1α might initiate Cd-elevated HMGA2 and PHGDH. Collectively, HIF-1α-elevated HMGA2 regulated PHGDH transcriptionally by binding to the PHGDH promoter, resulting metabolic reprogramming from OXPHOS to glycolysis, which mediated Cd-induced cell migration. This study potentially offers a new approach for prevention of lung cancer.